2018
DOI: 10.1159/000493392
|View full text |Cite
|
Sign up to set email alerts
|

Sauna Bathing and Risk of Psychotic Disorders: A Prospective Cohort Study

Abstract: Objective: Sauna bathing has been suggested to promote mental well-being and relaxation, but the evidence is uncertain with respect to mental disorders. We aimed to assess the association of frequency of sauna bathing with risk of psychosis in the Kuopio Ischemic Heart Disease prospective population-based study. Subjects and Methods: Baseline sauna bathing habits were assessed in 2,138 men aged 42–61 years who had no history of psychotic disorders. Participants were classified into three groups based on the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 30 publications
0
18
0
2
Order By: Relevance
“…Of the two, we included the study with the longer follow-up 34 . Consequently, four studies were included in meta-analysis 28 , 30 , 31 , 34 . Please see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the two, we included the study with the longer follow-up 34 . Consequently, four studies were included in meta-analysis 28 , 30 , 31 , 34 . Please see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The studies had an average follow-up length of 14.55 years (SD = 7.58) for psychosis after CRP assessment at baseline. Two studies involved relatively young adults with psychosis from specific birth cohorts (mean age at outcome assessment around 24–26 years) 31 , 34 , while two involved older adults (mean age at the outcome of 64–78 years) 28 , 30 . Samples were, on average, 60.2% male (range: 44.5–100%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In respect to specific effects on mental health outcomes from sauna, there is overwhelming anecdotal evidence from traditional folklore (46), but minimal scientific or sociological evidence. In the same Finnish cohort discussed above, there was found to be a strong association between frequent sauna bathing and a reduction of psychotic disorders after a median follow-up of 25 years (51), but this is the only longitudinal evidence currently available. Other studies have suggested a positive effect of mood from a Korean “jjimjilbang” sauna (52, 53), as well as reduction of pain intensity in chronic conditions such as hypertension headaches (54).…”
Section: Firementioning
confidence: 92%